Low Anterior Resection Syndrome (LARS) and Related Factors Variation Pattern in Indonesian Tertiary Hospital: Case-Controlled Study - Jeo, Wifanto Saditya; Mazni, Yarman; Putranto, Agi Satria; Primadhani, Wendy; Ananti, Anggini T.; Yoladifa, Safira Farah (http://dharmais.co.id/, 2025)
Background: Dysfunctional bowel movement, also referred to as low anterior resection syndrome (LARS), is a regular issue correlated with rectal cancer, which significantly impacts overall wellbeing. Thisstudy intended to look for the LARS incidence in patients with colorectal cancer where rectal preservation was not possible and identify factors affecting major LARS incidence in Indonesia. Method: This study follows a case-control design. Patients with rectal cancer over 18 years old who underwent tumour removal with mesorectal excision and colorectal anastomosis at Dr. Cipto Mangunkusumo General Hospital, Indonesia, from January to March 2019. The control group includes patients of eligible age who had anal sphincter preservation, stoma closure, and fall into the No LARS or Minor LARS category. Data were collected from medical records and scored with a validated LARS questionnaire. Results: Among 40 patients included, 42.5% had major LARS. The surgical procedure of low anterior resection (LAR) was significantly associated with 31.7% of major LARS patients (p = 0.04). Preoperative radiotherapy [OR 0.1 (0.02–0.49)] and anastomosis levels [OR 0.07 (0.01–0.39)] were associated with major LARS. The ROC curve revealed an AUC of 0.77, indicating significant results with the threshold for anastomosis level was 5 cm. Biofeedback revealed group differences in resting anal and maximal squeeze pressures, indicating sphincter impairment and preoperative treatment impact LARS progression. Conclusion: Major LARS development was heightened by surgical methods, preoperative radiotherapy, and lower anastomotic levels, emphasizing the role of sphincter dysfunction and preoperative interventions in LARS development.